Questioning Privilege: Tools for Research and Teaching - Sarah Ray; Jill Zarestky (Adult Education Research Conference, 2016)
Privilege and bias are important concepts for researchers and educators to examine, as part of doctoral training and as professional experiences develop. In this session, we explore tools and strategies for furthering awareness of privilege and bias for academics at all stages and for personal, research, and instructional use.
Keywords: social justice; critical theory; qualitative research